A methodology for modelling traffic related emissions in suburban areas - Toşa, Cristian; Antov, Dago; Köllő, Gavril; Rõuk, Harri; Rannala, Marek (Transport, 2015)
A methodology that integrates a computer program COPERT III for calculation of traffic emissions estimates, and a transportation modelling software CUBE VOYAGER was used to assess pollutant emissions for a suburban area, as a support for future transport planning strategies to be applied for any developing road network. COPERT III is used to obtain the carbon monoxide emission factors by accounting for the car fleet composition, characteristics and average speed. An aggregated emission parametric equation was determined and used further on for estimating network carbon monoxide emissions based upon the output of macroscopic traffic characteristics enabled by traffic simulation software, CUBE VOYAGER. The methodology and modelling results are applied here for Floreşti, a satellite town of Cluj-Napoca, Romania. First published online: 16 Oct 2013